2020
DOI: 10.20546/ijcmas.2020.903.253
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Diversity Analysis for Grain Micronutrients Concentration, Yield and Agro-morphological Traits in Pearl millet (Pennisetum glaucum (L) R. Br.)

Abstract: Micronutrient malnutrition resulting from the dietary deficiency of important minerals such as Iron (Fe), Zinc (Zn), Copper (Cu) and Manganese (Mn) in the staple food crops like pearl millet leads to ubiquitous food-related health problems. In context to this present investigation was undertaken to study the phenotypic diversity among 48 maintainer (B) and restorer lines (R) of pearl millet genotypes for grain micronutrients concentration, yield and agro-morphological traits using multivariate approach. Higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 21 publications
5
13
0
1
Order By: Relevance
“…DIKSHIT and SHIVARAJ (2015) and KAUR et al (2018) also reported that linseed accessions did not necessarily assemble into the same cluster based on their geographical origins. Clustering of linseed accessions together regardless of their source supports the possibility of a common progenitor but separation by geographical or ecological isolation mechanisms as reported by KUMAR et al (2020) in pearl millet. The genotypes from the different geographical location falls under different clusters didn't rules out the pollen-mediated gene flow in linseed (JHALA et al, 2011) and ryegrass (MAITY et al, 2021).…”
Section: Fatty Acid Compositionsupporting
confidence: 70%
See 1 more Smart Citation
“…DIKSHIT and SHIVARAJ (2015) and KAUR et al (2018) also reported that linseed accessions did not necessarily assemble into the same cluster based on their geographical origins. Clustering of linseed accessions together regardless of their source supports the possibility of a common progenitor but separation by geographical or ecological isolation mechanisms as reported by KUMAR et al (2020) in pearl millet. The genotypes from the different geographical location falls under different clusters didn't rules out the pollen-mediated gene flow in linseed (JHALA et al, 2011) and ryegrass (MAITY et al, 2021).…”
Section: Fatty Acid Compositionsupporting
confidence: 70%
“…High heritability coupled with high genetic advance for yield and related traits were reported in linseed by AKBAR et al, 2003;TADESSE et al, 2010;MIRZA et al, 2011;KUMAR et al, 2012;SIVARAJ et al, 2012;DIKSHIT and SIVARAJ, 2015;CHANDRAWATI et al, 2016;YOU et al, 2017;KAUR et al, 2018;DHIRHI and MEHTA, 2019. Grouping of genotypes into few numbers of homogenous clusters facilitates the selection of diverse lines for the hybridization purpose. It permits precise comparison among all the possible pairs of genotypes and provides an opportunity for bringing together gene constellations and yielding transgressive segregants from crossing between diverse lines (KUMAR et al, 2020). The distribution of 50 linseed genotypes into nine different clusters revealed considerable differences among linseed genotypes for yield and various morphological characters.…”
Section: Fatty Acid Compositionmentioning
confidence: 99%
“…The extent of phenotypic variation of the QTNs varied from R 2 = 1.8% for QTN-SOLRN at Chr 6A-AX-95244609 to R 2 = 38.6% for QTN-SOLRN at Chr 3B-AX-95150666. The highest number of QTNs was identified in chromosome 7B (44) followed by 6A (34), 3B (33), 7A (31), 1D (31), 2B (29), 1B (29) and 6B (27). Further, among the total 456 QTNs, 87 QTNs and 27 QTNs were repeatedly detected by two, three or more ML-GWAS models, respectively.…”
Section: Genome-wide Association Studiesmentioning
confidence: 96%
“…In contrast to the conventional QTL approach, the AM approach enables screening of a large number of alleles present in natural populations of species, thus providing greater resolution mapping of a target trait. In the past couple of years, AM has been widely applied to map traits in many crop species including wheat, rice, barley (Hordeum vulgare L.), maize and soybean (Glycine max L. Merril) [21,[24][25][26][27] with the availability of high-throughput genotyping and phenotyping platforms [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Among the phenotypic, biochemical, and molecular methods [8,9] employed in the assessment of genetic diversity, the phenotypic method is a relatively inexpensive approach. A number of research efforts have utilized agromorphological traits as a singular approach or in combination with molecular markers to characterize and study the diversity of maize populations [10,11,12].…”
Section: Introductionmentioning
confidence: 99%